Analisis Dampak Pembangunan Bendungan Karian pada Aspek Perubahan Sosial Ekonomi Masyarakat Desa Sukarame Kecamatan Sajira Kabupaten Lebak-Banten - Juwandi, Ronni; Nida, Qotrun; Bisri, Lutfia Fauziah (Al-DYAS, 2023)
Development in a region is certainly inseparable from the participation of all parties in the region. This becomes important when changes in an area will have a direct impact on all components in that area, including the community. Karian Dam is a megaproject of Banten Province which is located in Lebak Regency. Precisely in four sub-districts in Lebak Regency including Sajira, Maja, Cimarga, and Rangkasbitung Districts. Based on the data obtained by the researchers, the researchers chose Sukarame Village as the research location because the number of heads of families affected by the construction of this dam was counted the most among other villages in Sajira District. Of which there were 519 residents who not only lost their homes, but also other life support facilities such as rice fields, and others. Researchers want to find out more about the impacts that have arisen after the construction of the Karian Dam on the aspect of socio-economic change in the people of Sukarame Village, Sajira District, Lebak Regency, Banten. This study uses a type of descriptive qualitative method with data collection techniques of interviews, observation, and documentation. From this it was found that the welfare state of the community after land acquisition became worse for most of the community because the people of Sukarame Village had to lose their jobs as farmers and did not have the opportunity to work in other fields due to inadequate human resources, and had to lose traditions or habits. which has been attached for a long time due to the relocation of a new place of residence. In fact, the key word for compensation is stated in Law No. 2 of 2012 concerning "Land Procurement for Development in the Public Interest".